Green Japan : environmental technologies, innovation policy, and the pursuit of green growth - Holroyd, Carin (Japan and global society., 2018)
"As climate change continues to threaten both our economic and ecological well-being, countries around the world are trying to implement green strategies that will simultaneously curb emissions and spur economic growth. Green Japan critically examines the Japanese effort to combine economic growth with commitments to environmental sustainability. Carin Holroyd explores green growth strategies in various industries including conservation, energy, urban development, and international trade. Holroyd's comprehensive analysis of how innovation strategies connect with environmental priorities combines a detailed study of government policies with insightful assessments of consumer and market responses. The unevenness of Japan's success clearly demonstrates the exceptional technological innovation and creative public policy initiatives that are needed in order to successfully reverse the effects of climate change. Green Japan offers a nuanced and hopeful account of one nation's attempts at linking environmental sustainability and continued prosperity."--